Portrait of a 'real' marero: Fantasy and falsehood in stories of gang violence. (September 2019) - Wayne Fontes, Anthony
In 21st-century Guatemala transnational gangs (or maras ) have become erstwhile emissaries of extreme peacetime violence, distilling in spectacular fashion the fear, rage, and trauma swirling around out-of-control crime. Young gang members (or mareros ) are drawn in by and work hard to recreate the phantasmagoric figure the maras cut in social imaginaries, linking the acts of violence gangs perform to the ways gang members – and myriad others – make sense of this violence. This article traces how collective fantasies about gangs are essential in the making of the 'real' marero by engaging with the oral history of a single informant: a former member of the Mara Salvatrucha named Andy who became a protected witness for the Guatemalan government. Through Andy's life and violent death, it illuminates how essential shared fantasies and falsehoods are in the production of knowledge about criminal terror, as well as in the production of violence itself.